Data on genome assembly and annotation of Marinobacter sp. strain CA1 isolated from indigenous diatom found in whiteleg shrimp pond in Malaysia - Muthukrishnan, Sarmila; Mohd-Padil, Hirzahida; Mohamed-Alipiah, Norfarrah; Natrah, Ikhsan (Elsevier, 2022)
Marinobacter is a genus belonging to the class Gammaproteobacteria and the family Alteromonadaceae. This genus is a Gram-negative bacterium which can be found in a wide range of marine and saline water environments. Here, we present the genome sequence of Marinobacter sp. strain CA1 that was isolated from the indigenous diatom found in the whiteleg shrimp, Penaeus vannamei (Bonne 1931) pond in Malaysia. Genome sequencing was done using Pacbio and Illumina sequencing platforms. De novo hybrid assembly based on Pacbio long reads and high quality Illumina short reads yielded a complete circular chromosome with 4.7 M base pair (bp) in size. This genome was submitted to Genbank, NCBI database and can be accessed under accession number: NZ_CP071785 and the BioProject acession number PRJNA710741. This data could be useful for other studies on microalgae and bacteria interaction, and comparative genomics analysis of other Marinobacter species.